The Empirical Relationship between Soil Resistivity and Soil Strength Parameters as an Alternative to Soil Investigation - Shiwakoti, Indira; Paudel, Tika Ram; Shakya, Ashish Ratna; Shrestha, Krishna Kumar; Thapaliya, Sobit; Pudasaini, Anil; Magar, Milan; Karki, Alina; Niraula, Saroj; Bhandari, Gopal (Journal of Nepal Geological Society, 2025)
The present study involves the correlation of field electrical resistivity with strength properties of soil along Sunwal to Lamahi section of New Butwal 400kv transmission line alignment. Geologically the area is located in Quaternary deposit of Terai plain and Siwalik. The objective of this study is to find out correlation and empirical relationships between field electrical resistivity with strength properties of soil such as Cohesion (c), Internal Angle of Friction (ø), Moisture Content (w), Bulk Density (d) and Fine Content (fc). To obtain the results, undisturbed samples from thirty six number of test pits up to 3.0m depth and five number of boreholes up to 10.0m depth were extracted by using split-spoon sampler. These samples were tested in the laboratory of Geological Investigation Department and soil strength parameters were calculated. The field resistivity values were computed by using Wenner Alpha arrangement. The resistivity values up to 10.0 m depth for boreholes and up to 3.0m depth of test pits were taken for the analysis. The results obtained were compared and correlated with soil strength properties obtained from boreholes and test pits. Results from both the laboratory tests and field electrical resistivity tests indicate that there is consistent in the correlation between the resistivity and soil strength properties. The regression plots of the electrical resistivity (ρ) values against each of the determined strength parameters shows an empirical relationship ø = 2.2167ln (ρ) + 19.671, c = 25.143e-0.005ρ, w = 131.52 ρ -0.499, d = 0.0009ρ + 1.1697 and fc = 83.256e-0.004ρ with Angle of Internal Friction, Cohesion, Moisture Content, Bulk Density and Fine Content respectively.